Palaeontological And Geological Highlights Of The Black Country UNESCO Global Geopark - Graham Worton; Colin Prosser; Jonathan Larwood (Geoconservation Research)
The Black Country UNESCO Global Geopark, located in central England, joined the Global Geopark Network in July 2020. It is the most urban Geopark in the network with a population of approximately 1.1 million people. Located in an area rich in raw materials (Carboniferous coal, iron, and clay; Silurian limestone), it was quarried and mined extensively to fuel the Industrial Revolution. These activities created exposures which contributed greatly to the development of geoscience, including the establishment of the Silurian System. It also revealed and led to the collection of a rich and extremely well-preserved fossil fauna from the Upper Carboniferous and especially from the Silurian Much Wenlock Limestone Formation, with trilobites, crinoids, and numerous other taxa from the Geopark adorning museum collections across the world. Internationally important geological exposures, surviving within what is now an extremely urban and populated setting, provide a range of challenges and opportunities, and these continue to drive innovation and good practice in geoconservation, education and tourism within the geopark, where robust conservation and management of Geosites is combined with innovative ways to engage with local communities and visitors. UNESCO Global Geopark status will play an important role in opening doors to make the Black Country’s geoheritage, including its paleontology, accessible to many more people.